TRANSLASI AUSLANDER-REITEN - MARIS, IKA METIZA (IAIN Batusangkar, 2012)
sequence in is far from obvious. To see the presence of this sequence, we need to know Auslander-Reiten translations, as a functor composition between standart duality and transpotision. This sequences is useful in representation theory of algebras especially in formation of Auslander-Reiten Quiver. This paper will discuss about Auslander-Reiten translation and how to construct Auslander-Reiten translation from a module. . In the end of this paper we will see about main properties of this translation. Key words : Auslander-Reiten translation, Auslander-Reiten sequences, Functor, Projective module